CHANGES IN REARFOOT STRIKE PATTERNS OVER CHILDHOOD: A 3-YEAR PROSPECTIVE LONGITUDINAL COHORT STUDY (Kinesiology, 2022)
Rearfoot strike (RFS) in children running produces impact forces that give rise to a transient stress wave traveling through the body. It could contribute to the development of injuries. The purpose of this study was to determine RFS prevalence during childhood while running at a self-selected velocity in a prospective longitudinal cohort study. A total of 175 children (68 girls), aged 6 to 14 years, participated in this study. The sample was divided into three age groups (age in 2016): 6-8 years, 9-11 years, and 12-14 years, which were analysed again three years later (2019). A 2D video-based analysis was used to record the RFS. Taking into account all samples, in the jogging trial the prevalence of RFS (an average of both feet) was 86.9% in 2016 and 94.7% three years later; in the running trial the prevalence was 82.6 and 94.4%, respectively. In all samples a significant increase of RFS prevalence was found in both the jogging and running trials for both feet over three years (jogging, left foot, p=.011, right foot, p=.023; running, left foot, p=.001, right foot, p